Analysis of Teacher Pedagogical Competency in Learning English for Santri Students at the Modern Islamic Boarding School Darussalam Kepahiang - Dedi Efrizal; Dedi Sofyan; Syafryadin Syafryadin (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: English learning still creates difficulties among students, marked by a lack of motivation and creativity of students. The purpose of this study is to analyze the pedagogic competence of teachers in learning English for students at the Modern Islamic Boarding School of Darussalam Kepahyang. Using qualitative descriptive methods, data collection techniques through observation, documentation and interviews. The data analysis technique follows Huberman's theory through three stages, namely data reduction, data presentation, and data verification as the stage of concluding. The results of the analysis can be concluded that the pedagogic competence of teachers in teaching English to students in Islamic boarding schools is generally at a good level, because English teachers have the skills to open classes, and have the ability to master learning materials and methods, and teachers have been able to manage classes, including closing learning. However, in the English learning process, there are still obstacles and obstacles, such as the lack of optimal student learning outcomes. So that it can be suggested to improve students' English learning, then increase the pedagogic competence of teachers in Islamic boarding schools.Keywords: Pedagogic Competence of Teachers, English Learning for Students, Pondok Pesantren Modern Darussalam Kepahiang. Abstrak: Pembelajaran bahasa inggris masih menciptakan kesulitan dikalangan santri, ditandai motivasi dan kreatifitas santri masih kurang. Tujuan penelitian ini untuk menganalisis kompetensi pedagogic guru dalam pembelajaran bahasa inggris santri di pondok pesantren Modern Darussalam Kepahyang. Menggunakan metode deskriptif kualitatif, teknik pengumpulan data melalui observasi, dokumentasi dan wawancara. Teknik analisis data mengikuti teori Huberman melalui tiga tahapan yaitu reduksi data, penyajian data, verifikasi data sebagai tahapan menyimpulkan. Hasil analisis dapat disimpulkan bahwa kompetensi pedagogik guru dalam mengajar bahasa Inggris siswa di pondok pesantren secara umum berada pada tingkat baik, karena guru bahasa Inggris telah memiliki keterampilan untuk membuka kelas, dan memiliki kemampuan menguasai materi dan metode pembelajaran, dan guru telah mampu mengelola kelas, termasuk menutup pembelajaran. Namun, dalam proses pembelajaran Bahasa inggris masih mengalami hambatan dan kendala, seperti kurang maksimalnya hasil belajar santri. Sehingga dapat disarankan untuk meningkatkan pembelajaran bahasa inggris siswa, maka tingkatkan kompetensi pedagogik guru di pondok pesantren.Kata kunci: Kompetensi Pedagogik Guru, Pembelajaran Bahasa Inggris Santri, Pondok Pesantren Modern Darussalam Kepahyang.